2014
DOI: 10.1039/c4an00506f
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical activation of diamond microelectrodes: implications for the in vitro measurement of serotonin in the bowel

Abstract: The electrochemical pretreatment of diamond microelectrodes was investigated for the purpose of learning how an anodic, cathodic or a combined anodic + cathodic polarization affects the charge-transfer kinetics for two surface-sensitive redox systems: ferri/ferrocyanide and serotonin (5-hydroxytryptamine, 5-HT). The pretreatments were performed in 0.5 mol L−1 H2SO4. The anodic pretreatment was performed galvanically for 30 s at 250 mA cm−2. The 10 cathodic pretreatment was performed for 180 s at −250 mA cm−2. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 40 publications
1
31
0
Order By: Relevance
“…A cathodic treatment was evidently effective to clean the electrodes, resulting in high repeatability of the current responses. The result confirmed to the application of cathodic treatment at BDD electrodes to improve their resistance for the detection of biochemical and pharmaceutical compounds 21–25. Further investigation at low pH showed that the oxidation peak could be well observed for the oxidation of adenosine monophosphate (AMP), adenosine diphosphate (ADP) and ATP at cathodically‐treated BDD, while it was only found for AMP at anodically‐treated BDD.…”
Section: Introductionsupporting
confidence: 61%
“…A cathodic treatment was evidently effective to clean the electrodes, resulting in high repeatability of the current responses. The result confirmed to the application of cathodic treatment at BDD electrodes to improve their resistance for the detection of biochemical and pharmaceutical compounds 21–25. Further investigation at low pH showed that the oxidation peak could be well observed for the oxidation of adenosine monophosphate (AMP), adenosine diphosphate (ADP) and ATP at cathodically‐treated BDD, while it was only found for AMP at anodically‐treated BDD.…”
Section: Introductionsupporting
confidence: 61%
“…Cathodic reactivation was indeed observed to be also more efficient in removing other types of contaminants from BDD electrodes when similar activation protocols were used . This was the case for instance for cleaning electrodes from fouling in human urine solution or more recently after electro‐oxidation of serotonin in an aqueous KCl supporting electrolyte . In the case of indole, only ∼50% of the signal was recovered after anodic activation, which might result from the difficulty in removing a thicker film of contaminant (polymer).…”
Section: Resultsmentioning
confidence: 94%
“…radicals at the electrode vicinity combined with the nonproduction of oxidized indolic compounds may explain the reactivation efficiency here. In addition to the removal of organic matter over the electrode surface, the reactivation process may also lower the surface carbon–oxygen functionality coverage by introducing surface hydrogen, as suggested by other teams when similar reactivation processes were used , and therefore increasing further the electrode reactivity. Cathodic reactivation was indeed observed to be also more efficient in removing other types of contaminants from BDD electrodes when similar activation protocols were used .…”
Section: Resultsmentioning
confidence: 99%
“…They demonstrated that pretreatment did not increase surface roughness or detachment of the diamond coating from the Pt wire substrate. 226 Diamond microelectrodes are resistant to fouling by serotonin and they are now routinely used to measure serotonin release in the enteric nervous system. 227 Recently thin-film diamond electrodes have been used for FSCV measurements.…”
Section: Electrochemical Detection Of Neurotransmittersmentioning
confidence: 99%